Systematic Literature Review: Ethnomathematics Research Trends Using Bibliometrix R Studio Biblioshiny (2005-2025) - Dhea Wulantika; Sumin (Tadris Matematika, 2026)
This study aims to analyze the trend of scientific publications on the theme of ethnomathematics indexed by Scopus during the period 2005-2025. The analysis is conducted as a basis for identifying future research directions and opportunities. The method used is Systematic Literature Review (SLR) with the help of bibliometric analysis using R Studio through the biblioshiny interface. Data was collected automatically through the Scopus API with the keyword “ethnomathematics”, which resulted in 670 documents from journals, books, book chapters and others. Furthermore, publication patterns, author collaboration, journal distribution, and thematic trends were analyzed. Data visualization through biblioshiny provides a comprehensive picture of research dynamics, which can be used as a strategic reference for the development of further studies in this field. Trends in the topics of equations, ethnomathematics, mathematics education, and curricul from the derivatives of this theme are also still largely unexamined so it is important that there is novelty related to further research on the theme of ethnomathematics.